Physiologically Based Pharmacokinetic Models for Adults and Children Reveal a Role of Intracellular Tubulin Binding in Vincristine Disposition - Christine M. Lee; Nicole R. Zane; Gareth Veal; Dhiren R. Thakker (Wiley, 2019)
Vincristine is a cytotoxic chemotherapeutic agent used as first‐line therapy for pediatric acute lymphocytic leukemia. It is cleared by hepatic oxidative metabolism by CYP3A4 and CYP3A5 and via hepatic (biliary) efflux mediated by P‐glycoprotein (P‐gp) transporter. Bottom‐up physiologically based pharmacokinetic (PBPK) models were developed to predict vincristine disposition in pediatric and adult populations. The models incorporated physicochemical properties, metabolism by CYP3A4/5, efflux by P‐gp, and intracellular binding to β‐tubulin. The adult and pediatric PBPK models predicted pharmacokinetics (PK) within twofold of the observed PK parameters (area under the curve, terminal half‐life, volume of distribution, and clearance). Simulating a higher hypothetical (4.9‐fold) pediatric expression of β‐tubulin relative to adult improved predictions of vincristine PKs. To our knowledge, this is the first time that intracellular binding has been incorporated into a pediatric PBPK model. Utilizing this PBPK modeling approach, safe and effective doses of vincristine could be predicted.